IoT-Linked Integrated NFC and Dual Band UHF/2.45 GHz RFID Reader Antenna Scheme - Adisak Romputtal; Chuwong Phongcharoenpanich (My University, 2019)
This research proposes a system board of integrated antenna scheme of near-field communication (NFC) and dual band ultra-high frequency (UHF, 920-925 MHz)/2.45 GHz radio frequency identification (RFID) reader antennas for Internet of Things (IoT) applications. The integrated antenna scheme is capable of simultaneous execution of NFC and UHF RFID functions whereby the NFC and UHF RFID modules, which are serially connected to a microcontroller with Wi-Fi module (NodeMCU), read the universal identification (UID) of NFC and UHF RFID tags. The data are then forwarded to a cloud server via Internet of Things (IoT) and are viewable on smartphones using Blynk mobile application via IoT. To realize the optimal antenna design, simulations were carried out using CST Studio Suite. Prototype antennas were subsequently fabricated and integrated into the system board for IoT-linked near- and far-field communication. The simulation and measured results are in good agreement. The NFC reader antenna resonates at 13.56 MHz, and the dual band UHF/2.45 GHz RFID reader antenna achieves the 920-925 MHz and microwave (MW) bands with high isolation. The novelty of the proposed integrated NFC and UHF RFID antenna scheme lies in the use of cloud technology to store real-time and archival data, in place of traditional servers. The integrated antenna scheme could achieve the NFC, UHF, and MW frequency bands, rendering it ideal for IoT applications.
Keywords: Near Field Communication; RFID technology advancements